Dual Role of Endogenous Serotonin in 2,4,6-Trinitrobenzene Sulfonic Acid-Induced Colitis - Rapalli, Alberto; Bertoni, Simona; Arcaro, Valentina; Saccani, Francesca; Grandi, Andrea; Vivo, Valentina; Cantoni, Anna M.; Barocelli, Elisabetta (Frontiers in Pharmacology, 2016)
Background and Aims: Changes in gut serotonin content have been described in Inflammatory Bowel Disease and in different experimental models of colitis: the critical role of this monoamine in the pathogenesis of chronic gastrointestinal inflammation is gradually emerging. Aim of the present study was to evaluate the contribution of endogenous serotonin through the activation of its specific receptor subtypes to the local and systemic inflammatory responses in an experimental model of Inflammatory Bowel Disease. Methods: Colitis was induced by intrarectal 2,4,6-TriNitroBenzene Sulfonic acid in mice subacutely treated with selective antagonists of 5-HT1A (WAY100135), 5-HT2A (Ketanserin), 5-HT3 (Ondansetron), 5-HT4 (GR125487), 5-HT7 (SB269970) receptors and with 5-HT1A agonist 8-Hydroxy-2-(di-n-propylamino)tetralin. Results: Blockade of 5-HT1A receptors worsened TNBS-induced local and systemic neutrophil recruitment while 5-HT1A agonist delayed and mitigated the severity of colitis, counteracting the increase in colonic 5-HT content. On the contrary, blockade of 5-HT2A receptors improved global health conditions, reduced colonic morphological alterations, down-regulated neutrophil recruitment, inflammatory cytokines levels and colonic apoptosis. Antagonism of 5-HT3, 5-HT4 and 5-HT7 receptor sites did not remarkably affect the progression and outcome of the pathology or only slightly improved it. Conclusions: The prevailing deleterious contribution given by endogenous serotonin to inflammation in TNBS-induced colitis is seemingly mediated by 5-HT2A and, to a lesser extent, by 5-HT4 receptors and coexists with the weak beneficial effect elicited by 5-HT1A stimulation. These findings suggest how only a selective interference with 5-HT pro-inflammatory actions may represent an additional potential therapeutic option for intestinal inflammatory disorders.